Effects of biochar on ethanol-type and butyrate-type fermentative hydrogen productions. (June 2020) - Li, Weiming; He, Lei; Cheng, Chi; Cao, Guangli; Ren, Nanqi
Graphical abstract: Highlights: Rice straw biochar boosted ethanol and butyrate type fermentative H2 productions. 3 g/L biochar was the optimal dosage for both two fermentation types. H2 production increased 118.4% in ethanol-type and 79.6% in butyrate-type. Biochar boosted substrate conversion, buffered pH and lowered the redox potential. Biochar immobilized cells and released mineral nutrients to boost H2 production. Abstract: Low hydrogen yield was the bottleneck of dark fermentative hydrogen production. To solve this problem, the effects of rice straw-derived biochar on hydrogen production was investigated in different fermentation types. Ethanol-type and butyrate-type fermentations, two dominant types of dark fermentation, were carried out in batch fermentations with different concentrations of biochar. The results revealed that 3 g/L was the best concentration for both types of fermentations. Hydrogen production increased by 118.4% and 79.6% in ethanol-type and butyrate-type fermentations, respectively. The maximal hydrogen yields of ethanol-type and butyrate-type fermentations were 1.34 and 2.36 mol/mol-glucose, respectively. The addition of biochar buffered the broth pH, lowered the redox potential, and released mineral nutrients. The porosity of biochar boosted cell immobilization and thus improved the H2 productivity. This study demonstrated the enhancement effect of biochar on ethanol- and butyrate-type fermentative hydrogen productions, and enhanced the understanding of the functional mechanisms of biochar.